Comparison of published core outcome sets with outcomes recommended in regulatory guidance from the US Food and Drug Administration and European Medicines Agency: cross sectional analysis. Issue 1 (3rd November 2022) - Saldanha, Ian J; Dodd, Susanna; Fish, Rebecca; Gorst, Sarah L; Hall, Deborah A; Jacobsen, Pamela; Kirkham, Jamie J; Trepel, Dominic; Williamson, Paula R
Abstract : Objective: To compare the outcomes in published core outcome sets with the outcomes recommended in corresponding guidance documents from the European Medicines Agency (EMA) and US Food and Drug Administration (FDA), matched by health condition. Design: Cross sectional analysis. Setting: US and Europe. Population: Sample of core outcome sets related to drugs, devices, and gene therapy that involved patients in the consensus process, published between 1 January 2015 and 31 December 2019; and corresponding EMA and FDA guidance documents. Main outcome measures: The extent of matches between outcomes included within core outcome sets and those recommended in corresponding EMA and FDA guidance documents were assessed. Matches were considered to be general (ie, non-specific) or specific (ie, exact). General matches were assessed to determine whether the core outcome set or guidance document outcome was narrower. Results: Relevant guidance documents were found for for 38 (39%) of 98 eligible published core outcome sets. Among outcomes in core outcome sets, medians of 70% (interquartile range 48-86%) and 52% (33-77%) were matches with outcomes recommended in EMA and FDA documents, respectively. Medians of 46% (27-68%) and 26% (18-46%) were specific matches with outcomes in EMA and FDA documents, respectively. When outcomes were generally matched, the outcomes from core outcome sets were more frequently narrower than the regulatory outcomes (83% and 75% for EMA and FDA, respectively). Conclusion: Greater adoption of, and reference to, core outcome sets in regulatory guidance documents can encourage clinical trialists, especially those in industry, to measure and report consistent and agreed outcomes and improve the quality of guidance. Given the overlap between outcomes in core outcome sets and regulatory guidance, and given that most core outcome sets now involve patients in the consensus process, these sets could serve as a useful resource for regulators when recommending outcomes for studies evaluating regulated products. Developers are encouraged to appraise recommended outcomes in salient regulatory documents when planning a core outcome set.